2021
DOI: 10.1007/s40620-021-01170-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cognitive impairment and related risk factors in hemodialysis patients

Abstract: Background Cognitive impairment in hemodialysis patients has been acknowledged over the last years and has been reported in up to 80% of patients. Older age, high prevalence of cardiovascular risk factors, such as stroke and transient ischemic attack, uremia, and multiple metabolic disturbances represent the most common factors for cognitive impairment in hemodialysis patients. Methods We conducted a prospective cohort study on 408 patients from 10 hemodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 51 publications
(70 reference statements)
2
19
2
Order By: Relevance
“…We use a more comprehensive neurocognitive test battery, which is then also able to establish a neurocognitive profile in individuals after kidney transplantation. A recently published study showed a high prevalence of cognitive impairment in dialysis individuals [5], examined by the CERAD Test battery [43].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We use a more comprehensive neurocognitive test battery, which is then also able to establish a neurocognitive profile in individuals after kidney transplantation. A recently published study showed a high prevalence of cognitive impairment in dialysis individuals [5], examined by the CERAD Test battery [43].…”
Section: Discussionmentioning
confidence: 99%
“…We extended this questionnaire to include stress levels before and after testing prior to planned transplantation by the item "How stressed do you feel at the moment?" (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Stress Experiencementioning
confidence: 99%
See 3 more Smart Citations